The relationship among flexibility, aerobic fitness, leg extension power and agility with lower extremity injuries in footballers - Afsharnezhad, T.; Sefatian, A.; Burbur, A. (International Journal of Sports Science and Engineering, 2011)
Eagerness to soccer has been increased considerably during the last decade. The increasing popularity of this sport has increased the probability of injuries. The risk of being injured in professional football is very high. The purpose of this study was to consider the relation among flexibility, muscle power, agility and aerobic fitness with lower extremity injury rates, and to quantify and determine the nature, and sites of injuries in soccer players. 60 male players who participated in the Iranian professional league were studied prospectively in a non-randomized controlled trial over football semi-seasons. Data were recorded by each team`s athletic trainer on forms provided by the investigators. Physical fitness was assessed by sit-and-reach test, Sargent vertical jump test, and Astrand step test in the beginning of the survey. The data were statistically analyzed using a chi-square analysis to determine whether any of the factors had a relation to the incidence of injury. Statistical significance was noted by a P level of less than 0.05. Totally, 101 injuries were recorded. Bruising (30.7%) and sprains (20.8%) were the major injury types, the leg and ankle only being the site of 43.2% of the injuries reported. The results of this study showed a significant relationship between flexibility and agility with muscle cramp. Furthermore, this relation between flexibility and sprains was significant. Nevertheless, there was no significant relation between other physical fitness components and other injuries. More injuries occurred to the dominant leg. Professional football players are exposed to a high risk of injury and there is a need to investigate ways of reducing this risk. In this study, the number of lower extremity cramp and strain injuries was significantly fewer in player with increased flexibility. Flexibility and agility should be improved in football players by regular preseason programs.